2019
DOI: 10.1108/jstpm-11-2018-0105
|View full text |Cite
|
Sign up to set email alerts
|

Mobile marketing technology adoption in service SMEs: a multi-perspective framework

Abstract: Purpose The popularity and use of mobile marketing technologies or devices have led to significant interest from researchers and practitioners, particularly in small- and medium-sized enterprises (SMEs), where these technologies offer significant benefits to SMEs given the poor human capital and financial constraints encountered. The use of mobile marketing devices assists SMEs to boost their sales promotion strategies which aim at increasing the sales of their products and services. However, there has been li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 92 publications
1
73
0
Order By: Relevance
“…Studies that investigated issues about SMEs in Nigeria have always adopted approaches used by scholars in the developed world as if Nigeria operates the same culture with those in developed nations.This research focuses on microbusinesses in Nigeria because they are growing rapidly, representing 99 per cent of micro, small and medium enterprises (Kale, 2017) and contribute mainly to Nigeria national output (Eze and Chinedu-Eze, 2018). More specifically, the research centred on service micro-businesses because Nigerian economy is serviceoriented and the sector today is regarded as primary economic driver for digital marketing, and the substantial efforts to expand Nigerians economy is largely dependent on the service sector (Rantapuska and Ihanainen, 2008;Eze et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies that investigated issues about SMEs in Nigeria have always adopted approaches used by scholars in the developed world as if Nigeria operates the same culture with those in developed nations.This research focuses on microbusinesses in Nigeria because they are growing rapidly, representing 99 per cent of micro, small and medium enterprises (Kale, 2017) and contribute mainly to Nigeria national output (Eze and Chinedu-Eze, 2018). More specifically, the research centred on service micro-businesses because Nigerian economy is serviceoriented and the sector today is regarded as primary economic driver for digital marketing, and the substantial efforts to expand Nigerians economy is largely dependent on the service sector (Rantapuska and Ihanainen, 2008;Eze et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Alshamaila et al (2013) and Tornatzky and Fleischer (1990), these three dimensions provides both limitations and opportunities for the advancement of technological innovation and shape the manner to which micro-businesses implement new technology. Also, Eze et al (2019) argued the TOE framework is a very important analytical tool that unravels both the drivers and inherent features of innovation, proficiencies and other environmental circumstances of the adoption organisations. Besides, many studies (see Eze and Chinedu-Eze, 2018b;Maclennan and Van Belle, 2014;Ruivo et al, 2014;Nuryyev et al 2020) have used the TOE framework.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The results indicated that ICT capabilities determined 57% variance of agricultural products marketing. Therefore, the following null hypotheses were formulated: H0 1 : There is no significant relationship between the use of social media in agricultural marketing and cost of marketing agricultural products H0 2 : There is no significant relationship between the use of social media (Facebook, WhatsApp and Instagram) in agricultural marketing and farmers' turnover from agricultural products Other related studies are "use of information communication technologies among agricultural extension officers in Lesotho" (Akintunde & Oladele, 2019), "adoption of agricultural e-marketing," (Alavion et al, 2017), as well as the studies of Eze et al (2019), among others. 2016investigated the effect of social media on the performance of advertisement business in in Kenya.…”
Section: Empirical Reviewmentioning
confidence: 99%